Isokinetic specific tension of quadriceps in sprinters, distance runners and normal young adults - Cheung, C. K.; Hong, Y. (17. International Symposium on Biomechanics in Sports, 1999)
The purpose of this study was to determine whether isokinetic specific tension differences existed between athletes of different sports. Nine sprinters, eight distance runners and nineteen young adults were recruited as subjects in this study. A Cybex dynamometer was employed to measure the isokinetic peak torque of knee extension at 80o/sec, 120o/sec, 180o/sec, 240o/sec and 300o/sec. The cross sectional area of quadriceps was measured using the anthropometic equation of Housh et al. (1995). There was no significant difference between isokinetic specific tension of quadriceps in sprinters, distance runners and normal young adults. The result of this study indicated no significant difference in isokinetic specific tension between subject groups. Therefore, when the equation: Torque specific tension x cross sectional area was used to predict the magnitude of peak muscle torque vector in sprinters and distance runners, the specific tension of them can be assumed to be equal.